Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.1 - Simplifying Rational Expressions - Exercise Set: 51

Answer

$\dfrac{4-x^{2}}{x-2}=-x-2$

Work Step by Step

$\dfrac{4-x^{2}}{x-2}$ Factor the numerator: $\dfrac{4-x^{2}}{x-2}=\dfrac{(2-x)(2+x)}{x-2}=...$ Change the sign of the denominator. To do so, also change the sign of the fraction. After that, simplify: $...=-\dfrac{(2-x)(2+x)}{2-x}=-(2+x)=-x-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.